2004
DOI: 10.1079/phn2004624
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of herbal teas made from the leaves of comfrey (Symphytum officinale): reduction of N-oxides results in order of magnitude increases in the measurable concentration of pyrrolizidine alkaloids

Abstract: Objectives: To determine the relative quantities of two hepatotoxic pyrrolizidine alkaloids, symphytine and echimidine, in teas prepared from comfrey leaves (Symphytum officinale), and to determine the potential contribution of the N-oxide forms of these alkaloids to levels of the parent alkaloids. Design: Comfrey leaves were purchased from three commercial sources and used to prepare tea in a manner consistent with the methods used by consumers. An extraction scheme was devised for extraction of the alkaloids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…As demonstrated, ordinary preparation of herbal beverages from PA-containing plant parts will result in beverages containing PAs and PANOs of the used plant material (Oberlies et al, 2004). Methods or studies to alter or reduce the PA-content of herbal infusions are not available.…”
Section: Food Processingmentioning
confidence: 99%
“…As demonstrated, ordinary preparation of herbal beverages from PA-containing plant parts will result in beverages containing PAs and PANOs of the used plant material (Oberlies et al, 2004). Methods or studies to alter or reduce the PA-content of herbal infusions are not available.…”
Section: Food Processingmentioning
confidence: 99%
“…Previous studies have shown that comfrey possesses numerous beneficial properties due to the presence of many compounds with biological activity. But unfortunately, the studies have also shown that this herb is also potentially toxic due to the presence of toxins in comfrey which include pyrrolizidine alkaloids (PAs) such as lycopsamine, echimidine and lasiocarpine, and their N-oxides [24,25]. Based on this, it can be concluded that the determination of the composition of the aqueous extract of comfrey root is of great importance.…”
Section: Uhplc-dad-hesi-ms Analysis Of the Aqueous Extract Of Comfreymentioning
confidence: 99%
“…[33,46]). Also, some studies have shown that certain botanical products contain not only varying beneficial constituents, but also varying ones [47,48]. Therefore, it is necessary that authors of trials of herbal interventions completely describe the product used.…”
Section: F Practitionermentioning
confidence: 99%